Digital methods in weed control - Schwartau, V.; Mykhalska, L.; Zozulya, O. (Quarantine and plant protection, 2024)
Goal. Explore the components of digital technologies to increase the efficiency of weed control and crop productivity, reduce the cost of cultivation technologies, and ensure the environmental safety of herbicide use. Methods. The Normalised Differential Vegetation Index (NDVI) of the crops was determined using the Cropwise Operation satellite monitoring service In field conditions, NDVI values were determined with the GreenSeeker device (Trimble Agriculture). Chlorophyll content in plant leaves was measured using a SPAD-502 field chlorophyll meter (Konica Minolta, Japan). The stress index Y(II) or real quantum yield of electron transport, which estimates the effective quantum yield of photochemical energy conversion to FSII, was determined using a field fluorometer Y(II) meter & Plant Stress Kit (Opti-Science, USA). The results were statistically processed. Results. Examples of the use of digital technologies in crop production to improve weed control systems are presented. Sprayers with intelligent systems for identification of weeds and targeted application of herbicides are being actively implemented in crop production. It has been shown that the combination of flumetsulam + florasulam herbicides effectively controls dicotyledonous weeds such as Lözelii’s dry rib, wild poppy, pink thistle, etc. For the determination of chlorophyll content (the value of the SPAD index) one week after treatment, the differences between the treated variant and the control were not removed. No significant differences were also found in the NDVI values. At the same time, the stress indicator Y(II), or the real quantum yield of electron transport of FSII, is quite sensitive and informative for determining differences in photosynthetic activity of weed plants and, accordingly, for a general rapid assessment of the efficacy/selectivity of the herbicide on the crop. An example of the use of satellite data to assess the weediness of a field is presented. In the early stages of maize development, a high level of NDVI index (0.4—0.5) was observed when weeds were actively developing, and correspondingly high levels of crop vegetation index were recorded. The NDVI value of the crop in the field changed significantly after the herbicide application: the index value decreased rapidly to 0.25—0.30. Multispectral (satellite) imagery can therefore be used to produce maps of weeds in fields during the early development of wide-row crops, allowing farmers to identify areas with high levels of weed infestation and apply targeted measures in good time. Conclusions. The use of digital methods to improve weed control systems is an integral part of the development of cultivation technologies in modern crop production. Digital methods make it possible to reduce the use of herbicides, lower the cost of cultivation technologies, increase yields and develop agriculture towards sustainable and environmentally friendly production. The development of multispectral approaches in the identification of plant species is promising not only for the improvement of weed control with herbicides, but also for the operational determination of the presence/emergence of resistant weed biotypes in the fields. The implementation of digital technologies (diginomics) or digitalization is a key component of the development of modern crop production on the way to increasing the profitability, productivity and quality of the crop for reducing the impact of agricultural production on ecosystems, as well as for significantly reducing the costs of growing technologies.